Synthesis and Characterization of Gold@Gold(I)-Thiomalate Core@Shell Nanoparticles - Corthey, Gastón (2010)
In this paper, the synthesis of gold@gold(I)−thiolate core@shell nanoparticles is described for the first time. The chemical nature and structure of these nanoparticles were characterized by a multi-technique approach. The prepared particles consist of gold metallic cores, about 1 nm in size, surrounded by stable gold(I)−thiomalate shells (Au@Au(I)−TM). These nanoparticles could be useful in medicine due to the interesting properties that gold(I)−thiomalate has against rheumatoid arthritis. Furthermore, the described results give new insights in the synthesis and characterization of metallic and core@shell nanoparticles.